Anemia is a poor prognostic factor for stage I non-small cell lung cancer (NSCLC) patients treated with Stereotactic Body Radiation Therapy (SBRT). (May 2019) - Pathak, Rima S.; Pantarotto, Jason R.; Cook, Graham; Holmes, Oliver; Cross, Peter; MacRae, Robert M.
Highlights: This study reports on the prognostic ability of haematological parameters for the largest known biopsy-proven stage-I medically inoperable cohort treated with SBRT. After SBRT, the median values of Hb, ALC, ANC and TPC declined whereas the NLR and the PLR increased as compared to pre-SBRT. Anemia along with other parameters was found to be a poor prognostic factor for local control despite treatment with SBRT to doses of >100 Gy BED10 . Simple and minimally invasive methods like a peripheral blood sample can provide prognostic information even for stage-I NSCLC patients. Patient, tumor and treatment factors along with molecular markers should be used to create risk stratification models that can guide therapy.